2012
DOI: 10.1111/j.1525-1594.2012.01443.x
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular Assist Device Support in Children and Adolescents With Heart Failure: The Children's Medical Center of Dallas Experience

Abstract: Children with heart failure unresponsive to medical therapy are left with few options for survival. Ventricular assist devices (VADs) are life-saving options for such patients, allowing for bridge to transplantation or cardiac recovery. Retrospective review of cases from May 2006 to October 2010 was undertaken. Fourteen patients underwent implantation of VADs for refractory heart failure. Mean age was 9 years (range 1-17 years), and weight was 41 kg (range 9.7-71 kg). Indications for support: end-stage cardiom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…All of these occur in the context of normal systolic function of the systemic single ventricle. VAD use in the systemic circulation is therefore not a suitable solution for “Fontan failure.” 17, 18 To support the pulmonic circulation, VAD implant requires complex cannulation, 19 and is currently reported only anecdotally, 20, 21 often without successful outcome. 22 Novel pump designs have been proposed specifically for Fontan patients to address this problem, 19, 23 with the expectation that successful utilization may favorably impact transplant candidacy and outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of these occur in the context of normal systolic function of the systemic single ventricle. VAD use in the systemic circulation is therefore not a suitable solution for “Fontan failure.” 17, 18 To support the pulmonic circulation, VAD implant requires complex cannulation, 19 and is currently reported only anecdotally, 20, 21 often without successful outcome. 22 Novel pump designs have been proposed specifically for Fontan patients to address this problem, 19, 23 with the expectation that successful utilization may favorably impact transplant candidacy and outcome.…”
Section: Discussionmentioning
confidence: 99%
“…We did not study children, in whom unique issues are often raised, though bridging to transplant with VAD has been done successfully. 21, 35 …”
Section: Discussionmentioning
confidence: 99%
“…Fraser et al (21) reported a 57% incidence of infectious complications in BH patients. In HeartWare patients, the reported incidence of infections of the driveline exit site varies between 7 and 47% (22,23). The first four patients (44.4%) in our group with the HeartWare system presented with infection of the driveline exit site.…”
Section: Infectious Complicationsmentioning
confidence: 69%
“…We believe that this reflects on ongoing learning curve as more and more pediatric VADs are used. 2,4,11,12,14,15 It appears that patient age is a significant driver for choice of pharmacotherapy. For example, enoxaparin was more frequently used in younger patients, likely because of the difficulty of warfarin management in this patient group.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6] Indications for VAD support include myocarditis, inherited cardiac myopathies, dilated cardiomyopathy, acute rejection of heart transplantation, and congenital heart disease. 2,4,7,[9][10][11][12][13] Anticoagulation in pediatric VAD patients has likely undergone an evolution as best practices, and ideal methods are elucidated based on clinical experience.…”
mentioning
confidence: 99%